DDRE-01. CDK PATHWAY INHIBITION WITH ABEMACICLIB IMPROVES INTRACRANIAL AND EXTRACRANIAL RESPONSE TO CHECKPOINT BLOCKADE IN PRE-CLINICAL MODELS OF MELANOMA BRAIN METASTASIS. (12th November 2021) - Nayyar, Naema; Singh, Mohini; de Sauvage, Magali; Dahal, Ashish; Brehm, Michael; Brastianos, Priscilla
Abstract: While immune checkpoint inhibitors (ICI) have revolutionized treatment of metastatic melanoma, few of the 75% of patients who develop brain metastases benefit from immunotherapy. Inhibition of CDK4/6 pathway – altered in 90% of melanoma patients – can reportedly increase tumor inflammation and sensitize extracranial tumors to ICI. To determine whether intracranial melanoma can be similarly sensitized, we studied efficacy of combination CDK4/6 inhibitor Abemaciclib and ICI in immunocompetent mouse models of melanoma brain metastases bearing concurrent intracranial and extracranial tumors. 8-week-old female C57BL/6 mice received subcutaneous injections of 2x10 5 YUMM1.7 or B16-F10 melanoma cells 3 days prior to intracranial injections of 5x10 4 YUMM1.7 cells or 5x10 3 B16-F10 cells respectively. Mice were randomized into 6 treatment groups (n=5-7/group): Abemaciclib alone, anti-PD-1 monotherapy, anti-PD-1 and anti-CTLA4 combined (combination ICI), Abemaciclib and anti-PD-1, Abemaciclib combined with anti-PD-1 and anti-CTLA4 (triple therapy), and treatment with vehicle and isotype-matched antibodies as control. In mice bearing YUMM1.7 tumors, subcutaneous tumor growth was significantly reduced compared to control in mice treated with Abemaciclib alone ( p < 0.05), combination ICI ( p < 0.05) and triple therapy ( p < 0.05). However, improvement in survival was only observed with triple therapy ( p =0.039) compared to control group. In mice bearing B16-F10 tumors, we observed striking reduction in subcutaneous tumor growth in mice treated with Abemaciclib and anti-PD-1 compared to control-treated mice ( p =0.0016) or to mice receiving anti-PD-1 monotherapy ( p =0.000056). This further corresponded to a significant increase in survival of Abemaciclib and anti-PD-1 treated mice compared to control ( p =0.02). Additionally, we observed improved survival in mice treated with combination ICI ( p =0.006) or triple therapy ( p =0.01). These results indicate CDK4/6 inhibition with Abemaciclib can improve both extracranial and intracranial responses to ICI and sensitize melanoma brain metastases to immunotherapy. Our pre-clinical findings warrant further investigation to determine whether this combination approach can improve patient outcomes.